Eğitim Fakültesi Birinci Sınıf Öğrencilerinin Üniversite Yaşamına Uyumları: Akran Desteğinin Yordayıcı Rolü - Öztürk, Nilgün (Muş Alparslan Üniversitesi, 2020)
This study was conducted to investigate the role of peer support predicts the level of universtiy adaptation of first year university students. In this study, correlational survey method was used. Study samle of the research consisted of 468 students from the faculty of educational sciences. University Life Adaptation Scale and Peer Support Scales were used for data collection. Data obtained from the research were analysed by Simple Linear Regression Analysis and Pearson Moments Multiplier Correlation Coefficient. As a result of the study, it was determined that there was a positive and meaningful relationship between students'adaptation to university life and peer support. The results showed that peer support was predictors adaptation to university life. Findings were discussed under the light of literature.

Bu araştırma, akran desteğinin üniversite birinci sınıf öğrencilerinin üniversiteye uyum düzeylerini yordamadaki rolünü incelemek amacıyla yapılmıştır. Araştırmada ilişkisel tarama yöntemi kullanılmıştır. Araştırmanın örneklemini 468 eğitim fakültesi öğrencisi oluşturmaktadır. Veri toplama aracı olarak “Üniversite Yaşamına Uyum Ölçeği” ve “Akran Desteği Ölçeği” kullanılmıştır. Verilerin analizi için Basit Regresyon Analizi yöntemi ve Pearson Momentler Çarpımı Korelasyon Katsayısı kullanılmıştır. Çalışmanın sonucunda, öğrencilerin üniversite yaşamına uyumları ile akran desteği arasında pozitif yönde ve anlamlı ilişkilerin olduğu belirlenmiştir. Bulgular, akran desteğinin üniversite yaşamına uyumu anlamlı bir şekilde yordadığını göstermiştir. Bulgular alan yazın ışığında tartışılmış ve ileride yapılacak araştırmalara yönelik bazı önerilerde bulunulmuştur.
Adaptation of Freshmen of Faculty of Education to University Life: Predictive Role of Peer Support
anemon
Keywords: Adaptation to university life; University first-year students; Peer support; Üniversite yaşamına uyum; Birinci sınıf öğrencisi; Akran desteği